Staff Guidance Note on the Fund's Engagement with Countries in Fragile Situations. (Policy Papers; Policy Paper ;, 2012)
This note aims to provide country teams with broad guidance on engagement with countries in fragile situations. The aim of the guidance note is to help staff maintain focus on issues specific to countries in fragile situations. While engagement should focus on the issues and principles laid out in the note, there is, of course, scope for staff to tailor engagement to country specific circumstances beyond proposed practices.